Transformer Oil and Coil Winding Temperature Monitoring System using IoT - Enggu, Eunice Felicia; Yahaya, Jabbar Al-fattah (Evolution in Electrical and Electronic Engineering, 2022)
The transformer is a vital component of an electrical system. A variety of factors, such as transformer temperature, must be monitored and examined to keep the transformer in good working order. However, doing it conventionally by deploying a person to monitor and examine could result in measurement errors due to human mistakes. This study presents a review of IoT (Internet of Things) based on the temperature of oil and coil winding monitoring. The purpose of the temperature monitoring system implement remotely is to do the process of monitoring by using Arduino and a temperature sensor. ThingSpeak is a platform used in this system in which the data collected will be stored in the cloud. The data collected is then validated and thus the purpose of the IoT system is to work satisfactorily.